2018
DOI: 10.1101/gr.231183.117
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale identification of cellular pathways required for cell surface recognition

Abstract: Interactions mediated by cell surface receptors initiate important instructive signaling cues but can be difficult to detect in biochemical assays because they are often highly transient and membrane-embedded receptors are difficult to solubilize in their native conformation. Here, we address these biochemical challenges by using a genome-scale, cell-based genetic screening approach using CRISPR gene knockout technology to identify cellular pathways required for specific cell surface recognition events. By usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…Likewise, we also predicted a 3'UTR-protein complex formed with the nascent protein RHAMM/HMMR, a regulator of the stability of the mitotic spindle in normal cells 8,10 that acts as an extracellular CD44ligand promoting cell motility and invasion in cancer cells 10 , IGF2BP2, involved in mRNA storage and transport, and the Dynactin subunit 1 (DCTN1) as intermediate, a protein present at the "spindle" as well as at the "membrane" and notably involved in the transport of organelles and vesicles by tethering the dynein cargo to the microtubule 39 . We can thus hypothesize that the 3'UTR-RHAMM complex plays a role in the molecular mechanism allowing the extracellular localization of RHAMM in tumor cells.…”
Section: Archetypal Moonlighting Proteins Are Predicted To Form 3'utrmentioning
confidence: 99%
“…Likewise, we also predicted a 3'UTR-protein complex formed with the nascent protein RHAMM/HMMR, a regulator of the stability of the mitotic spindle in normal cells 8,10 that acts as an extracellular CD44ligand promoting cell motility and invasion in cancer cells 10 , IGF2BP2, involved in mRNA storage and transport, and the Dynactin subunit 1 (DCTN1) as intermediate, a protein present at the "spindle" as well as at the "membrane" and notably involved in the transport of organelles and vesicles by tethering the dynein cargo to the microtubule 39 . We can thus hypothesize that the 3'UTR-RHAMM complex plays a role in the molecular mechanism allowing the extracellular localization of RHAMM in tumor cells.…”
Section: Archetypal Moonlighting Proteins Are Predicted To Form 3'utrmentioning
confidence: 99%
“…Since that the binding assay results suggested that the G6b-B ligand was primarily composed of HS glycans, we opted to confirm and extend these finding by using a genome-scale cell-based CRISPR knockout (KO) screening approach, identifying all genes required for the synthesis and cell surface display of the G6b-B ligand (Sharma, Bartholdson, Couch, Yusa, & Wright, 2018). We observed that a fluorescently labelled highly-avid recombinant G6b-B binding reagent robustly stained several human cell lines providing the basis for a cellular genetic screen (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…We observed that a fluorescently labelled highly-avid recombinant G6b-B binding reagent robustly stained several human cell lines providing the basis for a cellular genetic screen (Figure 3A). A genome-wide mutant cell library was generated by transducing Cas9-expressing HEK293 cells with a library of lentiviruses each encoding a single gRNA from a pool of 90,709 individual gRNAs targeting 18,009 human genes (Sharma et al, 2018). Transduced cells that had lost the ability to bind to the recombinant protein were isolated using fluorescent-activated cell sorting and genes required for cell surface binding of G6b-B were identified by comparing the relative abundance of gRNAs in the sorted versus unsorted control population (Li et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by carefully designing the screening parameters, for example by generating marker lines specific to the biological process of interest, other facets of cellular signalling processes such as differentiation, motility, proliferation, metabolism and immunity can also be studied with this tool (refer to Table 1 of [ 14 ]). We have recently been working on devising a genome-wide KO screen that can be used to identify low-affinity interactions mediated by the receptors present on the surface of the cells [ 67 ] (unpublished). The field of identification of low-affinity receptor-ligand interactions has been challenging owing to the transient nature of such interactions, which make them difficult to detect in many existing biochemical methods.…”
Section: Conclusion and Further Directionsmentioning
confidence: 99%